Forecasting life expectancy in São Paulo City, Brazil, amidst the COVID-19 pandemic - Maria L. Miranda; Cassio M. Turra; Ugofilippo Basellini (Population Health Metrics)
Abstract Background The COVID-19 pandemic has significantly increased mortality rates, disrupting historical trends and making it challenging to forecast future life expectancy levels. São Paulo, the first city in Brazil to report a COVID-19 case and death, saw a decrease of over four years in life expectancy at birth for males and over three years for females between 2019 and 2021. São Paulo has been at the forefront of the demographic transition in the country and experienced a nonlinear mortality decline over the twentieth century. The city's historical mortality trajectory and the disruptive effects of COVID-19 have introduced challenges to mortality forecasting. Methods In this study, we used a unique dataset dating 1920–2022 to forecast life expectancy in São Paulo until 2050 using the Lee-Carter and Lee-Miller methods. Mortality rates were obtained from a combination of deaths gathered by the SEADE Foundation (SEADE) and population collected by the Brazilian Institute of Geography and Statistics. To mitigate the dependency on the fitting period's choice and better incorporate the effects of the recent mortality shock, we used different baseline periods, using all years from 1920 to 1995 as the starting year of the analysis and six scenarios for post-pandemic mortality levels. Prediction intervals were derived from simulated trajectories of the models' time indices. Based on 73,200 simulations for each year between 2023 and 2050, we synthesized the resulting life expectancy forecasts into median values and 95% prediction intervals (PI). Results By 2050, we predict that life expectancy at birth in São Paulo will reach approximately 81.4 years for men and 88.3 years for women. Also, within the 95% PI, we estimated that by 2045, male life expectancy could reach the levels of best-performing countries. Conclusions Our approach is among the first attempts to forecast mortality in the presence of shocks. Additionally, by evaluating different baseline periods, we advocate for the adoption of more accurate forecasting strategies, particularly in contexts of recent mortality decline. These findings provide valuable resources for policymakers and researchers working to address public health challenges arising from the pandemic and plan for the future well-being of many populations.